Algeria : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2013)
In this paper, the statistical appendix lists details regarding the supply and use of resources at current prices, sectoral breakdown of GDP at current prices, sectoral breakdown of real GDP growth, production export and consumption of oil products, production export and consumption of gas products, domestic prices of main energy products, surface area of main crops, crop yields, livestock, industrial production index, ore production, consumer price index, household income, labor force, employment and unemployment, summary of central government operations, sector, et cetera.